Persuasion ability in children from 6 to 12 years old: relations to cognitive and affective theory of mind. - Barajas-Esteban, María Carmen; Linero-Zamorano, María José; Alarcón-Postigo, Rafael (Frontiers, 2022)
This study analyzes the relation between cognitive and affective components of theory of mind (ToM) in school-aged children and persuasion abilities. One-hundred forty-three normotypical school children aged 6 to 12 were administered cognitive and affective ToM tasks and one persuasion production task. A set of regression models showed that only the affective ToM component can predict both the persuasion total score and all its indicators´ scores. Children with a greater ability to attribute emotional mental states do not only produce a wider variety of persuasive arguments but also focused on the persuadee and those with mental-related content. Both Hidden Emotion and Belief-Emotion (negative) tasks have been predictive of persuasion total scores. This study provides data on specific contribution of cognitive ToM and affective ToM on indicators of variety and quality of persuasive arguments independently.
Keywords: Persuasión (Psicología); Filosofía de la mente; Persuasion; Cognitive theory of mind; Affective theory of mind; School age; Normotypical development